Two‐Dimensional Fullerene Assembly from an Exfoliated van der Waals Template. (27th April 2018) - Lee, Kihong; Choi, Bonnie; Plante, Ilan Jen‐La; Paley, Maria V.; Zhong, Xinjue; Crowther, Andrew C.; Owen, Jonathan S.; Zhu, Xiaoyang; Roy, Xavier
Abstract: Two‐dimensional (2D) materials are commonly prepared by exfoliating bulk layered van der Waals crystals. The creation of synthetic 2D materials from bottom‐up methods is an important challenge as their structural flexibility will enable chemists to tune the materials properties. A 2D material was assembled using C60 as a polymerizable monomer. The C60 building blocks are first assembled into a layered solid using a molecular cluster as structure director. The resulting hierarchical crystal is used as a template to polymerize its C60 monolayers, which can be exfoliated down to 2D crystalline nanosheets. Derived from the parent template, the 2D structure is composed of a layer of inorganic cluster, sandwiched between two monolayers of polymerized C60 . The nanosheets can be transferred onto solid substrates and depolymerized by heating. Electronic absorption spectroscopy reveals an optical gap of 0.25 eV, narrower than that of the bulk parent crystalline solid. Abstract : C60 ‐Bausteine wurden zu einem Festkörper zusammengefügt, und der resultierende hierarchische Kristall wurde als Templat für die Polymerisation seiner C60 ‐Monoschichten genutzt, die zu kristallinen 2D‐Nanoschichten exfoliert werden können. Die Nanoschichten können auf feste Substrate übertragen und durch Erhitzen depolymerisiert werden. Absorptionsspektroskopie offenbart eine optische Bandlücke von 0.25 eV, die schmaler ist als die des kristallinen Festkörpers.